Analysis of the design and construction of the maritime barrier at the Angra I plant (Research, Society and Development, 2020)
The strong thrust of hydraulic refrigeration pumps, which suck up water, which is needed to generate energy at the Angra I nuclear power plant, has been affecting the local fauna, especially sea turtles. In order to avoid the death of several sucked turtles, a project was carried out to build a sea barrier with the purpose of preserving the lives of the animals, guaranteeing the operation of the plant. The purpose of this research was to analyze the design and construction of the installed barrier and maintenance of metal nets (carbon grids) both to protect the plant and to prevent deaths of marine animals with a primary focus on turtles. The barrier demonstrated an efficiency compared to previous data avoiding any mortality after its construction, in conjunction with the project, there was also the dissemination of the barrier project as a means of raising awareness among residents of nearby communities, as well as anglers and the entire population of cities around the world. Under the environmental impact caused.